Consumption categories, household attention, and inflation expectations: Implications for optimal monetary policy - Alexander M. Dietrich (University of Tübingen, Faculty of Economics and Social Sciences, 2023)
What inflation measure should central banks target? This paper shows optimal monetary policy targets headline inflation if households pay limited attention to different consumption categories when forming inflation expectations. This result stands in contrast to standard rational expectations models, where optimal policy targets core inflation. The core inflation rate excludes volatile energy and food prices (non-core) from headline inflation. Using novel survey data on inflation expectations for disaggregated consumption categories, I find household expectations are disproportionately driven by beliefs about future non-core prices. I develop a sparsity-based rational inattention model to account for the empirical evidence. While forming inflation expectations, households pay attention to the volatile non-core components; the stable core inflation component receives little attention. Finally, I embed this framework into a multi-sector New Keynesian model to derive the optimal inflation target. In the model, targeting headline inflation is optimal, whereas a core inflation target would fail to stabilize the economy sufficiently.
urn:nbn:de:bsz:21-dspace-1383517
Keywords: C83; E31; E52; E70; 330; Households expectations; Survey; Monetary policy; Behavioral macroeconomics